DEIXIS IN BRUNO MARS’S DOO-WOPS & HOOLIGANS ALBUM - Ika Sapitriani; Sortha Silitonga (State University of Medan, 2016)
This study deals with the English. The objectives of this study are to analyze type of deixis and to find out the most dominant type of deixis in Bruno Mars’s Doo-Wops & Hooligans Album. This study was conducted by using descriptive qualitative method. The data of this research were taken from Bruno Mars’s song lyrics in the Doo-Wops & Hooligans album and 10 titles songs lyrics as the samples. The findings showed that there are five types of deixis found in Bruno Mars in the ‘Doo-Wops & Hooligans’ album, namely Person deixis with 616 occurrences (60,39%), Spatial deixis with 95 occurrences (9,31 %), Temporal deixis with 58 occurrences (5,68%), Social deixis with 75 occurrences (7,35%), Discourse deixis with 176 occurrences (17,25%). In this song lyrics of Bruno Mars tends to use Person deixis as the dominant type. The deictic “I” is dominantly used in Bruno Mars’s song lyrics. “I” refers to Bruno Mars as the singer, it means Bruno Mars wants to express her feelings to the listener by her songs.